Semen characteristics of breeding bulls at the Central Cattle Breeding and Dairy Farm of Bangladesh (Bangladesh Journal of Animal Science, 2012)
The experiment was conducted on 97 breeding bulls at the central cattle breeding and dairy farm, Savar, Dhaka to find out the physical and chemical properties of different bull semen. Out of 97 bulls, 9 were Local (L), 9 were Friesian (F), 13 were Sahiwal (SL), 12 were Local×Friesian (L×F), 10 were Sahiwal×Friesian (SL×F), 26 were Local×Friesian×Friesian (LF1×F), 18 were Local×Friesian× Friesian×Friesian (LF2×F) bulls. The semen of different crossbred and local bulls was examined for ejaculate volume, concentration, pH and motility percent of sperm before and after freezing. It was observed that, the maximum average ejaculate was obtained from SL×F and the mean value was 12.9 ml. However, the minimum average ejaculate was obtained from LF×F and the mean value was 7.4 ml. Before freezing, the maximum average sperm concentration was obtained from SL and the mean value was 1858.4 million/ml. The minimum average sperm concentration was obtained from LF1×F and the mean value was 1286.6 million/ml. The maximum average pH was obtained from LF2×F and the mean value was 6.5. The maximum average motility was obtained from SL and the mean value was 68.8%. However, the minimum average motility was obtained from L×F and the mean value was 63.7%. After freezing, sperm concentration, pH and motility reduced substantially irrespective of type of breed. It could therefore be inferred that freezing of semen should be undertaken with special care to maintain optimum semen quality.http://dx.doi.org/10.3329/bjas.v41i1.11968